Analysis of the distribution of microfractures and micropores within granitic rock using simultaneous polarization–fluorescence microscopy. Issue 8 (August 2020) - Yuguchi, Takashi; Usami, Akane; Ishibashi, Masayuki
Abstract: The analysis of the distribution of microfractures and micropores is important to accurately characterise mass transfer within a rock body. In this paper, a new 'simultaneous polarization–fluorescence microscopy' method is presented, which can be used to analyse the distribution of microscopic voids, including microfractures and micropores, in granitic rock. In this method, thin sections prepared with fluorescent dye are analysed under a polarizing microscope equipped with a fluorescent reflected light source. Using both the transmitted and the fluorescent light sources, both the distribution of microfractures and micropores, and petrographic characteristics (mineral occurrences) can be determined efficiently and simultaneously. The distribution of microfractures and micropores observed in images of granites obtained using simultaneous polarization–fluorescence microscopy is consistent with the distribution observed in backscattered electron images. The low magnification characterisation of the distribution of microscopic voids also provides targeting for subsequent studies including scanning electron microscopy under high magnification, chemical analysis, and image processing. Abstract : Earth Sciences, Geology, Microfracture, Micropore, Microscopic void, Simultaneous polarization-fluorescence, Microscopy, Thin section, Toki granitic pluton